(D−π−A)3−Type metal-free organic dye for dye-sensitized solar cells application. (November 2018) - Liao, Xiaoning; Zhang, Hai; Huang, Jianping; Wu, Guoqiang; Yin, Xiaoli; Hong, Yanping
Abstract: Three novel (D−π−A)3 −type metal-free organic dyes (PTZTC1 −3 ) along with a reference dye (RD −SC ) bearing a mono D−π−A unit, comprising 4-positon substituted phenyl coupled with phenothiazine as a donor, thiophene as a π-conjugated linker and cyanoacrylic acid as an acceptor, were synthesized. The UV–Vis absorption spectra in solution and on TiO2 film, electrochemical redox potentials, and the photovoltaic parameters including incident monochromatic photon-to-current conversion efficiency (IPCE), short-circuit current ( J sc ), open-circuit voltage ( V oc ), maximum power conversion efficiency ( η ), and electrochemical impedance spectroscopy (EIS) of the corresponding dye-sensitized solar cells (DSSCs) were further explored. Among the DSSCs fabricated with these dyes, the PTZTC3 sensitized cell showed a η of 6.09% under standard global AM 1.5 solar condition (100 mW cm −2 ) owing to its relatively higher IPCE, higher J sc, higher V oc and longer electron lifetime (τr ). Graphical abstract: Comparing to those of the dye RD−SC bearing a mono D−π−A branch, the dyes PTZTC1−3 containing three independent D−π−A branches exhibit tripled molar extinction coefficient, higher IPCE values and broader IPCE spectra response in the visible region, as well as higher density of D−π−A light-harvesting units absorbed on the surface of TiO2 . Among the DSSCs sensitized by these dyes, the cell based on PTZTC3 attained the best power conversion efficiency (PCE) due to the highest short-circuit current, open-circuit voltage and the longest electron lifetime of the device. Image 1 Highlights: Three novel organic phenothiazine dyes bearing three D-π-A chains (PTZTC1-3 ) were synthesized. Three separated light harvesting units were contained in one molecule. Compared to those of RD-SC, the UV–visible and IPCE spectra of PTZTC1-3 were enhanced remarkably. Because of its relatively higher J sc and higher V oc, the PTZTC3 based cell exhibits a maximum η.